Serum leptin, estradiol and testasterone concentrations in normal healthy fertile women with different weights (Tikrit Journal of Pharmaceutical Sciences, 2023)
Background: Leptin, the product of the ob gene, is a hormone secreted by adipocytes. Animals with mutations in the ob gene are obese, leptin affects not only nutritional homeostasis but also reproductive events. A prospective study was done to investigate serum leptin ,estradiol and testosterone levels in 100 fertile healthy women with regular cycle aged(18-45) years with different weights and to see the influence of obesity on these parameters , the correlation of leptin with body mass index ,waist hip ratio , estradiol and testosterone level was determined. Methods fasting blood samples were obtained for the measurement of all studied parameters. serum concentrations of leptin was measured using ( ELISA) , estradiol and testosterone concentrations measured by ( ELFA ) technique (enzyme linked fluorescent assay)by mividus, the body-mass index was deﬁned as the weight in kilo-grams divided by the square of the height in meters. Results: according to the body mass index (BMI), the women were divided in to 3 groups: Group (1) normal weight(30 women) with BMI≤24.9 kgm2 , group( 2) Overweight(30 women) with BMI=25-29.9 kgm2 , group ( 3) obese (40 women) with BMI≥ 30 kgm2. The mean value ±SD of the weight in normal weight group was (53±5)kg , of overweight group was(65.8 ± 4.7) and of obese group was(91.6±16) so there was a highly significant difference between the 3 groups (p-value=0.000) , the Mean ± SD of waisthip ratio in normal, over weight and obese groups were (0.79 ± 0.06, 0.81 ± 0.03 and 0.84 ± 0.05) respectively and there was significant difference between the 3 groups(p-value=0.04), the leptin mean ± SD of normal ,overweight and obese groups were(12.4±6.7, 18.2±5.8 and 24.4±16.4) respectively, and p-value =0.000. Estradiol mean±SD of normal ,overweight and obese groups were (46.2±30.2 ,54.6±25 and79.9 ±52.7)respectively ,p-value =0.03,Testosterone mean±SD of normal, overweight and obese groups were (0.14±0.06, 0.16±0.07 and 0.2±0.09)respectively, p-value =0.00. Conclusions. Leptin correlate significantly with BMI, WH ratio and estradiol level, the women with higher BMI(obese) has higher level of leptin, estradiol and testosterone so the leptin clearly appears to be linked to the reproductive system .